BMAL1 regulates MUC1 overexpression in ovalbumin-induced asthma. (April 2023) - Tang, Lingling; Zhang, Xiaona; Xu, Yanqiu; Liu, Li; Sun, Xianhong; Wang, Bohan; Yu, Keyao; Zhang, Hui; Zhao, Xia; Wang, Xiongbiao
Abstract: Asthma often presents with a daily rhythm; however, the underlying mechanisms remain unclear. Circadian rhythm genes have been proposed to regulate inflammation and mucin expression. Here, ovalbumin (OVA)-induced mice and serum shock human bronchial epidermal cells (16HBE) were used in in vivo and in vitro models, respectively. We constructed a brain and muscle ARNT-like 1 (BMAL1) knockdown 16HBE cell line to analyze the effects of rhythmic fluctuations on mucin expression. Serum immunoglobulin E (IgE) and circadian rhythm genes in asthmatic mice showed rhythmic fluctuation amplitude. Mucin (MUC) 1 and MUC5AC expression was increased in the lung tissue of the asthmatic mice. MUC1 expression was negatively correlated with that of the circadian rhythm genes, particularly BMAL1 ( r = −0.546, P = 0.006). There was also a negative correlation between BMAL1 and MUC1 expression ( r = −0.507, P = 0.002) in the serum shock 16HBE cells. BMAL1 knockdown negated the rhythmic fluctuation amplitude of MUC1 expression and upregulated MUC1 expression in the 16HBE cells. These results indicate that the key circadian rhythm gene, BMAL1, causes periodic changes in airway MUC1 expression in OVA-induced asthmatic mice. Targeting BMAL1 to regulate periodic changes in MUC1 expression may, therefore, improve asthma treatments. Highlights: Rhythm gene disorders in OVA asthmatic mice manifested by an increased amplitude of transcriptional oscillations. MUC1 was accompanied by rhythmic oscillations in asthma due to BMAL1 regulation. The serum IgE levels observed a rhythmic fluctuation in the OVA-challenged mice.